Astrocytic AEG-1 drives neuroinflammation and enhances seizure susceptibility - Yuzhou Chen; Yunbo Yu; Jinhao Kou; Honggang Qi; Canyu Zhang; Feiyu Wang; Lijie Zhou; Xuemei Liang; Kang Xu; Cong Zhang; Aifeng Zhang; Xiufang Liu; et al. (Neurobiology of Disease)
Astrocyte-elevated gene-1 (AEG-1), also known as metadherin (MTDH) has emerged as a potent oncogene expressed in cancers. An increasing body of evidence indicates AEG-1 plays a pivotal role in various brain pathophysiological processes. Abnormal expression of AEG-1 in astrocytes has been correlated with inflammatory response, suggesting a possible role of AEG-1 in the pathogenesis of inflammatory encephalopathy. Here, we analyzed single-cell RNA sequencing data to explore the heterogeneity of astrocyte subpopulations in a mouse model induced by lipopolysaccharide (LPS), and investigated the effect of astrocytic AEG-1 on lipopolysaccharide (LPS)-induced inflammatory response and seizure susceptibility in mice, as well as in an in vitro astrocyte culture model. Our single-cell RNA sequencing analysis reveals that AEG-1-expressing astrocyte subpopulation is associated with inflammatory responses. LPS-induced inflammatory response is accompanied by increased AEG-1 expression in astrocytes. Depletion of astrocytic AEG-1, however, suppressed LPS-induced neuroinflammation and high seizure susceptibility both in vivo and in vitro. Furthermore, we find that AEG-1 induces neuroinflammatory cytokine expression and enhances seizure susceptibility, which is dependent on NF-κB signaling pathway. These data identify an important role of astrocytic AEG-1 in LPS-induced neuroinflammation and high seizure susceptibility, demonstrating that AEG-1 mediates downstream neuroinflammatory and epileptic effect via NF-κB signaling pathway.